Cerebellar Structures and the Programming of Movement Sequences - Albrecht Werner Inhoff; Robert Rafal (Behavioural Neurology)
Two patients with unilateral damage to the medial and lateral cerebellum were examined to determine whether local structures in the cerebellum are used to execute programmed movement sequences. Both patients performed a sequential tapping task which required the execution of either a single keystroke or of a sequence of three keystrokes. Movements executed with the contralateral hand showed increases in response onset times as the movement sequence increased from one to three response elements (sequence length effect). Furthermore, noninitial response elements were executed considerably faster than sequence initial responses (position effect). Movements executed with the ipsilateral hand showed a different pattern of results. Damage to medial cerebellar structure had no qualifying effect but damage to the lateral cerebellar structure eliminated effects of sequence length and of response position. The results suggest that the lateral cerebellum is implicated in the execution of programmed manual movement sequences.